Relative Performance Analysis On Selected Public And Private Sector Banks: A Camel Model Approach - Hymavathi, Dr.Ch. (The journal of contemporary issues in business and government, 2021)
Public and Private Sector Banks play a dominant role in portraying the financial system of an economy. An Economy’s health can be determined by the conditions prevailing in the financial system. In order to maintain a healthy financial system, it is necessary to analyse the banks regularly for identification of their Strengths and elimination of the potential vulnerabilities. Banks act as fuel for smooth and efficient functioning of an economy’s financial system. The objective of my study is to assess and contrast the financial, operational and managerial health of selected public and private sector banks. For the purpose of the study only three public sectors banks which include State Bank of India, Bank of Baroda and Union Bank and three private sector banks which include HDFC, ICICI and Axis Bank are taken into consideration. CAMEL approach is considered for analysing and contrasting the performance of the banks. CAMEL stands for C-Capital Adequacy, A-Asset Quality, M-Management Efficiency, E-Earnings and L-Liquidity.